2014
DOI: 10.1021/jf403006c
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Phenolics in Leaves of Three Red Pepper (Capsicum annuum) Cultivars

Abstract: The antioxidant properties and phenolic profiles were first investigated in this paper on the leaves of three red pepper cultivars, Blackcuban (BCPL), Hongjinju (HPL), and Yeokgang-hongjanggun (YHPL). Of the ethanol extract of the three cultivars, BCPL showed potent antioxidant activities against the 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) and the 2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical. Nine antioxidative compounds from the red pepper leaves were isolated and identified as one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 42 publications
2
51
0
Order By: Relevance
“…It is noteworthy that pepper leaves are edible and traditionally used for cooking in Korea (Kim et al . ), suggesting that pepper leaves are safe for human health.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that pepper leaves are edible and traditionally used for cooking in Korea (Kim et al . ), suggesting that pepper leaves are safe for human health.…”
Section: Resultsmentioning
confidence: 99%
“…LG, which was isolated by chromatrographic methods from WEPL (Kim et al . ), was kindly gifted from Clinical Trial Center for Functional Foods in Chonbuk National University (Chonju, Republic of Korea). The LG content was 6.34% of the extract and its chemical structure was confirmed using 1 H‐NMR and 13 C‐NMR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because hydroxycinnamates and anthocyanins are known to have potent radical scavenging activity based on ABTS and DPPH radical scavenging experiments (Kim et al . ; Ali et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activities of byproducts in many plants have been investigated using various evaluation methods, such as DPPH, ABTS, FRAP, and ORAC (Taveira et al 2012;Kim et al, 2014;Zhen et al, 2016). Those studies reported that antioxidant data are meaningful at the sectional level and suggested that variations in antioxidant activities can be useful on an industrial scale.…”
Section: Discussionmentioning
confidence: 99%